(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
Al-Sayyid Mohammad Amim Al-Ihsan was one of the renowned scholars and personalities in Indian sub-continent in the nineteen century. He has a great role and significant contribution to spread various religious knowledge and education in the People’s Republic of Bangladesh. This research aims to discuss about his biography including academic and working life. The research also highlights his momentous efforts and achievements, contributions to the religious knowledge, especially to the Fiqh and Usul Al-Fiqh studies. The research concludes that Al-Sayyid Mohammad Amim Al-Ihsan was known as a great scholar and Researcher of Islamic Shariah in the light of the Sunni doctrine. السيّد محمد عميم الإحسان من الهداة الأعلام المبرزين في شبه القارّة الهندية في القرن التاسع عشر الميلاديّ. وله أثرٌ عظيمٌ ودورٌ كبيرٌ في نشر العلوم الشرعية والدراسات الإسلاميّة في جمهوريّة بنغلاديش الشعبيّة. وهذا البحث يهدف إلى الوقوف على الحياة العلمية والعملية للسيّد محمد عميم الإحسان، مع التعرّف على أبرز جهوده التي بذلها في خدمة الشريعة الإسلاميّة عامّةً، وفي الفقه الإسلامي وأصوله خاصّةً. وقد توصّل البحث إلى كون السيّد محمد عميم الإحسان عالماً كبيراً، وخادماً مخلصاً للعلوم الشريعة والدراسات الإسلاميّة بالتدريس والتأليف والخطابة